STRENGTHENING THE ROLE OF ACCOUNT REPRESENTATIVES IN OPTIMIZING STATE REVENUE: THE ROLE OF MODERATING INTERPERSONAL COMMUNICATION - Diah Ayu Pradnyani; M. Rudi Irwansyah; I Nengah Suarmanayasa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Government institutions are expected to deliver optimal performance as a manifestation of public accountability, particularly in providing services that are effective, efficient, and focused on achieving organizational targets. Employee performance, particularly that of Account Representative (AR), serves as a key factor in supporting the success of Badung Utara Tax Office in securing tax revenue through collections. This study aims to analyze the effect of work ability and workload on Account Representative performance and to examine the role of interpersonal communication as a moderating variable. The research employs a quantitative approach using a census method that covers the entire population of Account Representatives at Badung Utara Tax Office, consisting of 33 individuals. Data were collected through questionnaires and analyzed using statistical analysis techniques and SEM-PLS to examine both direct and moderating relationships among variables. The results indicate that work ability has a positive and significant effect on Account Representative performance, suggesting that adequate knowledge, skills, and job competence contribute to improved AR performance. On the other hand, workload has a negative and significant effect on Account Representative performance, as high task volume and job complexity may reduce work focus and accuracy. Furthermore, interpersonal communication was found to moderate the effect of work ability on AR performance but did not moderate the effect of workload on performance. These results show that interpersonal communication plays an important role in optimizing work ability but has not been able to overcome workload challenges. This research is expected to provide practical contributions for management in human resource management and serve as a foundation for formulating policies to improve employee performance on a sustainable basis.